International Employer Brand Management A Multilevel Analysis and Segmentation of Students' Preferences - Christiaans, Lena. (Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2013)
The increasing globalization of business activities forces companies to recruit highly skilled employees all over the world. In order to attract these talents, employers have to differentiate themselves through a unique employer brand, appealing to diverse target audiences. However, in the absence of research on international students<U+0019> preferences for employer characteristics, it is difficult for multinational companies to decide on a feasible degree of employer brand standardization. Lena Christiaans investigates the impact of between-country differences, e.g. differences in national culture or economic wealth, on students<U+0019> preferences in relation to the effects of within-country differences in individuals<U+0019> characteristics. Combined with a segmentation of the European graduate market, the results provide readers with insight into the development of employer value propositions for business and engineering target groups. Contents - Core Concepts of Employer Branding - Contributions from Cross-Cultural Research - Employer Branding Strategy - Multilevel Analysis Target Groups - Researchers and students in the fields of employer branding, corporate branding, management, marketing, communications - Managers and experts with focus on employer branding, HR marketing, HR, corporate communications About the Author Lena Christiaans obtained her doctorate at the Chair in Corporate Management at Universitt̃ Hohenheim and currently works as a reputation manager in the Corporate Communications department of a DAX-30-company in Dusseldorf.